Virome of Pseudostellaria heterophylla: Identification and characterization of three novel carlaviruses and one novel amalgavirus associated with viral diseases of Pseudostellaria heterophylla - Li, Yong; Liu, Sai; Guo, Kun; Ding, Wanlong; Wang, Rong (Frontiers in Microbiology, 2022)
Pseudostellaria heterophylla is a traditional Chinese herbal medicine, which has been cultivated for hundreds of years. Viral diseases of P. heterophylla occur widely and limit the yield and quality of this medicinal plant. In this study, five leaf samples of P. heterophylla with typical viral symptoms were collected from four main producing regions that are distributed in Fujian, Guizhou, and Anhui Provinces in China and analyzed by next-generation sequencing. Comprehensive bioinformatics analyses revealed that nine viruses in five genera Carlavirus, Potyvirus, Fabavirus, Cucumovirus and Amalgavirus infected P. heterophylla. Among these viruses, three novel and two known carlaviruses, tentatively designated Pseudostellaria heterophylla carlavirus 1, 2, and 3 (PhCV1, PhCV2, and PhCV3), Jasmine virus C isolate Ph (Ph-JVC) and Stevia carlavirus 1 isolate Ph (Ph-StCV1), respectively, were first identified in P. heterophylla. PhCV1-3 share a similar genomic organization and clear sequence homology with members in the genus Carlavirus and could potentially be classified as new species of this genus. The distribution of PhCV1-3, Ph-JVC, and Ph-StCV1 in four production regions in Fujian, Guizhou, and Anhui Provinces were determined. One novel amalgavirus, tentatively designated P. heterophylla amalgavirus 1 (PhAV1), was first identified in P. heterophylla. It had a typical genomic organization of the genus Amalgavirus. In PhAV1, the +1 programmed ribosomal frameshifting, which is prevalent in most amalgaviruses, was identified and used in the expression of RNA-dependent RNA polymerase (RdRp). Combined with a phylogenetic analysis, PhAV1 could potentially be classified as new species of the genus Amalgavirus. In addition, multiple Broad bean wilt virus 2 (BBWV2) variants, Turnip mosaic virus (TuMV) and Cucumber mosaic virus (CMV), which have been reported in P. heterophylla, were also detected in this study. This study increased our understanding of P. heterophylla virome and provided valuable information for the development of a molecular diagnostic technique and control of viral diseases in P. heterophylla.